Molecular characterization of African Swine fever viruses in Burkina Faso, Mali, and Senegal 1989–2016: Genetic diversity of ASFV in West Africa. Issue 5 (29th July 2021) - Minoungou, Germaine L.; Diop, Mariame; Dakouo, Marthin; Ouattara, Abdoul Karim; Settypalli, Tirumala Bharani K.; Lo, Modou M.; Sidibe, Satigui; Kanyala, Estelle; Kone, Yaya Sidi; Diallo, Moctar Sidi; Ouedraogo, Anne; Coulibaly, Kadiatou; et al.
Summary: African swine fever (ASF) has been endemic in sub‐Saharan Africa since the 1960s. Following its introduction in Senegal, in 1957, ASF steadily progressed through West Africa, reaching Burkina Faso in 2003, and later Mali in 2016. Despite the heavy burden of disease on pig production, little information is available on the genetic diversity of Africa swine fever virus (ASFV) in Burkina Faso, Mali and Senegal. Here, we used real‐time PCR ASFV to detect the ASFV genome in samples collected between 1989 and 2016, in Burkina Faso, Mali and Senegal, and conventional approaches for isolate characterization. The C‐terminal end of the p72 protein gene, the full E183L gene and the central variable region (CVR) within the B602L gene in ASFV genome were sequenced and compared to publicly available sequences. ASFV genome was found in 27 samples, 19 from Burkina Faso, three from Mali and five from Senegal. The phylogenetic analyses showed that all viruses belong to genotype I, with the ASFVs from Burkina Faso and Mali grouping with genotype Ia and ASFV serogroup 4, and those from Senegal with genotype Ib and the ASFV serogroup 1. The analysis of the CVR tetrameric tandem repeat sequences (TRS) showed four TRS variants in Burkina Faso, two in Senegal and one in Mali. The three countries did not share any common TRS, and all CVRs of this study differed from previously reported CVRs in West Africa, except for Senegal. Three of the five isolates from Senegal fully matched with the CVR, p72 and p54 sequences from ASFV IC96 collected during the 1996 ASF outbreak in Ivory Coast. This study shows the spread of the same ASFV strains across countries, highlighting the importance of continuous monitoring of ASFV isolates. It also calls for an urgent need to establish a regional plan for the control and eradication of ASF in West Africa.